Lying for money : how legendary frauds reveal the workings of the world - Davies, Dan (Economist) (Scribner, 2021)
"An entertaining, deeply informative explanation of how high-level financial crimes work, written with verve and wit by an industry insider and expert in the field Lying, fraud, and fiscal deception are a daily news item, and the list of well-known banks, companies, and multinational financial institutions prosecuted for such crimes seems never ending. Since money was created, people have tried to sell things that don't exist and buy things without paying for them. Or have said one thing and done another, producing illegal profits and mountains of fraudulent documentation to protect themselves. But the ways such crimes are accomplished fall into certain fascinating defined categories. In Lying for Money, veteran regulatory economist and market analyst Dan Davies presents an engrossing genealogy of monetary malfeasance, stretching from ancient Greece to the global pandemic of 2020, explaining the ways illegal decisions are rationalized, how the assumption of criminal risk is approved by corporations, and the surprisingly consistent methodologies of history's greatest financial crimes. From the Salad Oil Swindle of the 1960s to the downfall of Theranos, Davies shows us that all frauds belong to one of four categories (the "long firm," the "control fraud," counterfeiting, and market crimes) and operate on the same basic principles. The only elements that change are the victims, the scammers, and the terminology. A perfect book for professionals in finance, banking, law, business school students, investors, and anyone else interested in understanding how the labyrinths of fiscal deceit really work"--